On the true identity of Sergentomyia gemmea and description of a closely related species: Se. raynali n. sp. Issue 4 (3rd June 2019) - Depaquit, J.; Vongphayloth, K.; Siriyasatien, P.; Polseela, R.; Phumee, A.; Loyer, M.; Vol, A.; Varlot, G.; Rahola, N.; Brey, P. T.; Sutherland, I. W.; Hertz, J. C.; et al.
Abstract: Several species of Leishmania are responsible for leishmaniases in Thailand, although little is known about their transmission. Sergentomyia gemmea has been suspected several times to transmit Leishmania martiniquensis . Some captures carried out in Thailand and Lao People's Democratic Republic have emphasized the scarcity of Se. gemmea, comprising only 1% of the collected females. The sequencing of cytochrome B mtDNA of our specimens showed that our specimens are not grouped with other Se. gemmea previously deposited in GenBank. The latter are grouped with some Se. khawi and Se. hivernus that we processed in the present study. We suspect misidentifications and propose focusing on the most useful characters for identification of Se. gemmea based on the examination of type‐specimens. The examination of the ascoids exhibiting anterior spurs is the most important one. However, we also describe Se. raynali n. sp. exhibiting comparable spurs but differing from Se. gemmea by its original cibarium. Finally, the vectorial role of Se. gemmea appears very questionable in the absence of new evidence. Abstract : The most important morphological character for identifying Sergentomyia gemmea comprises the antennal ascoids exhibiting spurs. A new species close to Sergentomyia gemmea is described from Thailand: Sergentomyia raynali n. sp. Sergentomyia gemmea, considered as a potential vector of Leishmania martiniquensis in Thailand, has probably been misidentified several times and its vectorial role remains questionable.